2013
DOI: 10.1088/0954-3899/40/12/125102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the19F(p, α0)16O reaction at low energies and the spectroscopy of20Ne

Abstract: The investigation of the 19 F(p, α 0 ) reaction at low bombarding energies allows the study of the spectroscopy of the 20 Ne compound nucleus in an energy region where the existence of quartet excitations has been suggested in the literature. Moreover, this reaction plays a major role in the fourth branch of the CNO cycle since it is relevant for the correct description of the hydrogen burning of fluorine in stars. For these reasons, we decided to investigate the 19 F(p, α 0 ) reaction in the E p 0.6-1 MeV ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 30 publications
(146 reference statements)
7
67
0
Order By: Relevance
“…Our data for h = 150°and 170°are in very good agreement with the data given by Paneta et al [12] even with respect to the absolute values. More recent measurements [11] of the differential cross-section at 150°in the proton energy range between 600 and 1000 keV also showed a very good agreement to the results presented in [6,7]. A direct comparison with our results is not possible because the data are not available and, furthermore, the fine structure of the excitation function in that energy range was not in the focus of our work.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Our data for h = 150°and 170°are in very good agreement with the data given by Paneta et al [12] even with respect to the absolute values. More recent measurements [11] of the differential cross-section at 150°in the proton energy range between 600 and 1000 keV also showed a very good agreement to the results presented in [6,7]. A direct comparison with our results is not possible because the data are not available and, furthermore, the fine structure of the excitation function in that energy range was not in the focus of our work.…”
Section: Resultssupporting
confidence: 86%
“…Dieumegard et al [7] measured the cross-section for this reaction at 90°and 150°in great detail over a proton energy range of 300-2000 keV, by means of an automatic energy scanning system. More recently a detailed study for the energy range between 600 and 1000 keV and backscattering at 150°was performed by Lombardo et al [11]. Paneta et al [12] investigated a broad range of reactions including the one under consideration here but for high proton energies up to about 4 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…The main part of data that we included in the R-matrix analysis were obtained with an experiment done at the ttt3 tandem accelerator in Napoli [29]. Details concerning the experimental configuration are reported in Ref.…”
Section: Selection Of Experimental Datamentioning
confidence: 99%
“…However, the energy resolution was not enough for achieving a good separation between resonances, thus preventing an accurate estimate of the their total widths as well as the reaction rate. Most recently, Lombardo et al reported new direct measurement data [34,35] on the 19 F(p,α 0 ) 16 O reaction at the energy region of E c.m. =0.18-1 MeV, and found the deduced astrophysical S -factor ≈1.5-2 times larger than currently recommended one.…”
Section: (Pα 0 ) Channelmentioning
confidence: 99%